KAJIAN POPULASI BAKTERI VIBRIO SP. PADA TAMBAK BUDIDAYA UDANG VANAME (LITHOPENAEUS VANNAMEI) SISTIM SEMI INTENSIF DENGAN PERSENTASE PEMBERIAN PAKAN YANG BERBEDA - Arifuddin Tompo (OCTOPUS : JURNAL ILMU PERIKANAN, 2016)
The study of the population of Vibrio sp isolated from water and sediment in semi-intensive ponds with a different percentage of doses of feed carried on the pond size 2500 m2 as 8 plot consisting of 6 plots the treatment and 2 plots reservoir. Shrimp used size PL 12 with dense stocking 25 tail/m2 maintained for 100 days. The treatments tested were to compare the percentage of feed between day and night. Treatment A = 100% at day and 0% at night, treatment B = 60% at day and 40% during the night, treatment C = 80% at day and 20% during the night. Each treatment was repeated twice. The results showed that population of bacteria in the sediment pond were in the range of 106 to 1012 CFU /mL. While the population of bacteria in water was in the range of 103 to 109 CFU/mL. Populations of Vibrio sp. in the pond sediment for all treatments during the study were in the range of 103 to 105 CFU/ mL. While in aqueous media is still in the range of 101 to 103 CFU/mL for all treatments. In general, bacterial populations are found in both sediment and water pond on the media is still in a safe range for the growth of cultured organisms.